The Inability of the Indonesian Government to Ensure Restitution Payments for Human Trafficking Victims - Supanto; Januar Rahadian Mahendra (Indonesian Journal Publisher, 2025)
Victims of human trafficking experience an abstract position because, in criminal law, the disadvantaged party is the community. The Restitution that victims of human trafficking should receive is also not received by them. This article analyzes the factors causing the unpaid restitution rights for victims of human trafficking using normative and descriptive-analytical research methods to answer this problem. Four main factors cause unpaid restitution for victims of human trafficking, including the incompetence of law enforcement in handling cases involving restitution, the amount of restitution exceeding the perpetrator's financial ability, the lack of case development by the police so that only field actors are arrested while intellectual actors are not, and the difficulty of collecting evidence. The government's failure to guarantee the payment of restitution impacts the victims and the community because there are no legal consequences for perpetrators who do not pay restitution. The current legal framework exacerbates this because of the limited definition of human trafficking and the inclusion of restitution as an additional punishment. This has implications for perpetrators who prefer to serve imprisonment rather than pay Restitution, which can reach tens of millions of rupiah.